An atlas of protein phosphorylation dynamics during interferon signaling - Idoia Busnadiego; Marie Lork; Sonja Fernbach; Samira Schiefer; Nikos Tsolakos; Benjamin G. Hale (Proceedings of the National Academy of Sciences, 2025)
Interferons (IFNs, types I-III) have pleiotropic functions in promoting antiviral and antitumor responses, as well as in modulating inflammation. Dissecting the signaling mechanisms elicited by different IFNs is therefore critical to understand their phenotypes. Here, we use mass spectrometry to investigate the early temporal dynamics of cellular protein phosphorylation in a human lung epithelial cell-line as it responds to stimulation with IFNα2, IFNβ, IFNω, IFNγ, or IFNλ1, representing all IFN types. We report an atlas of over 700 common or unique phosphorylation events reprogrammed by these different IFNs, revealing both previously known and uncharacterized modifications. While the proteins differentially phosphorylated following IFN stimulation have diverse roles, there is an enrichment of factors involved in chromatin remodeling, transcription, and RNA splicing. Functional screening and mechanistic studies identify that several proteins modified in response to IFNs contribute to host antiviral responses, either directly or by supporting IFN-stimulated gene or protein production. Among these, phosphorylation of PLEKHG3 at serine-1081 creates a phospho-regulated binding motif for the docking of 14-3-3 proteins, and together these factors contribute to coordinating efficient IFN-stimulated gene expression independent of early Janus kinase/signal transducer and activator of transcription signaling. Our findings map the global phosphorylation landscapes regulated by IFN types I, II, and III, and provide a key resource to explore their functional consequences.